2022
DOI: 10.1136/bmjebm-2021-111846
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the magnitude of reporting bias in trials of homeopathy: a cross-sectional study and meta-analysis

Abstract: ObjectivesTo assess the magnitude of reporting bias in trials assessing homeopathic treatments and its impact on evidence syntheses.DesignA cross-sectional study and meta-analysis. Two persons independently searched Clinicaltrials.gov, the EU Clinical Trials Register and the International Clinical Trials Registry Platform up to April 2019 to identify registered homeopathy trials. To determine whether registered trials were published and to detect published but unregistered trials, two persons independently sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 61 publications
1
12
0
1
Order By: Relevance
“…4.4 and 4.5, that homoeopaths mischaracterise and cherry-pick the available evidence. Moreover, they do this against the background of an already distorted evidence base because they also selectively report their findings, as Gartlehner et al (2022) found in a recent cross-sectional study and meta-analysis. The authors systematically investigated the extent of reporting bias in trials on homoeopathy.…”
Section: Misreportingmentioning
confidence: 97%
“…4.4 and 4.5, that homoeopaths mischaracterise and cherry-pick the available evidence. Moreover, they do this against the background of an already distorted evidence base because they also selectively report their findings, as Gartlehner et al (2022) found in a recent cross-sectional study and meta-analysis. The authors systematically investigated the extent of reporting bias in trials on homoeopathy.…”
Section: Misreportingmentioning
confidence: 97%
“…Poor research practice may mean that the true impact of homeopathy is substantially overestimated, said an evidence review published in BMJ Evidence Based Medicine 4. Many clinical trials have not been registered, 38% remain unpublished, and the main outcome was changed in a quarter of those published.…”
Section: Homeopathymentioning
confidence: 99%
“…However, the between-group difference of effect estimates was not significant (meta-regression: SMD 0.39, 95% CI −0.09 to +0.87). 33 It is not clear why the trial #A93 of the Mathie 2017 MA (Lewith 2002, listed in Gartlehner 2022, Supplement Table 3 as 'not registered') was not included in these analyses.…”
Section: Additional Data: Gartlehner 2022mentioning
confidence: 99%
“…The 16 reports consisted in 6 primary publications of one [6][7][8]10,11 or two 9 MA, respectively; 2 published MA protocols 27,28 ; 7 publications of additional analyses 3,[29][30][31][32][33] and 1 error correction 34 (Table 3).…”
Section: Figure 1 Flow Diagram Of Identification Screening and Inclus...mentioning
confidence: 99%
See 1 more Smart Citation